Optimal overcurrent relay coordination: a review - Muhamad Hatta, Hussain; Siti Rafidah, Abdul Rahim, Dr.; Ismail, Musirin, Prof. Dr. (Malaysian Technical Universities Network (MTUN), 2013)
Malaysian Technical Universities Conference on Engineering and Technology (MUCET) 2012 organised by technical universities under the Malaysian Technical Universities Network (MTUN), 20th - 21st November 2012 at Hotel Seri Malaysia, Kangar, Perlis.